Correction: A comparative study on sulfide removal by HClO and KMnO4 in drinking water. Issue 1 (17th December 2020) - Huang, Yeju; Liu, Zaohong; Guo, Yuanyuan; Lin, Qin; Liao, Xiaobin; Qi, Huan
Abstract : Correction for 'A comparative study on sulfide removal by HClO and KMnO4 in drinking water' by Yeju Huang et al., Environ. Sci.: Water Res. Technol., 2020, 6, 2871–2880, DOI: ; 10.1039/D0EW00629G .